The traffic and temperature effect on the reflective cracking - Minhoto, Manuel (2008)
This paper presents a study on the influence of the effects of temperature variations, in comparison to the traffic effects, on the reflective cracking behavior. It intends to contribute to the improvement of the pavement overlay design methods which consider reflective cracking as one among distress criteria. The development of this study was based on the numerical simulation of the overlay behavior, through the implementation of numerical thermal and mechanical models based on the finite element, considering the simultaneous action of traffic and temperature variations and their influence on reflective cracking. For overlay design purposes, it is important to consider temperature variations in the evaluation of the overlay behavior produced by the reflective cracking. The expected performance of an asphalt rubber hot mix, produced by the wet process with 20% crumb rubber was compared to a conventional asphalt taking into account the performance of these mixes.